Combining Poetry and Science to Create Scientific "Thesis Poetry" as a Tool for the Communication of Science. Issue 4 (August 2019) - Tada, Mitsuru
Research scientists are expected to communicate their science to the lay public. However, lay people need scientific literacy in order to understand science. Both science and poetry are aspects of culture that connect people and might be able to expand their reach by incorporating elements of each other. "Thesis poetry" based on the IMRaD (Introduction, Methods, Results, and Discussion) scientific paper format could promote understanding and empathy between scientists and the lay public, and foster and improve scientific literacy. This article proposes a thesis poem format incorporating empirical and personal logic and data drawn from original papers as a tool for the communication of science.